Workshop of Disaster Resilience School for Geography Teachers in Banjarmasin - Parida Angriani; Eva Alviawati; Aswin Nur Saputra; M. Muhaimin; Herlina Herlina; Putri Handayani (LPPM Universitas Islam Sultan Agung, 2026)
Banjarmasin is highly vulnerable to floods and residential fires, highlighting the urgency of integrating disaster education into school curricula. This community service program aimed to strengthen geography teachers’ capacity in promoting the concept of Disaster-Resilient Schools. The workshop applied a participatory approach, combining interactive lectures, group discussions, disaster simulations, and the development of school action plans. Geography teachers from Banjarmasin were actively involved throughout the sessions. Findings indicate significant improvement in teachers’ knowledge of disaster mitigation and preparedness, as well as enhanced skills in designing disaster-resilient school programs. Participants also demonstrated strong motivation to integrate disaster-related topics into geography lessons and to foster contextual learning strategies relevant to local risks. Based on questionnaire responses and reflective discussions at the end of the workshop, the participating geography teachers gave highly positive feedback on the program’s implementation. Most teachers stated that the materials delivered were relevant to classroom needs and aligned with the disaster vulnerability context in Banjarmasin.